Combination of Papeda (Metroxylon Sp) and Warm Androgynus Sauropus Compress to Toward Production of Breast Milk - Adriana Egam; Harlinah Harlinah (Institute of Computer Science (IOCS), 2022)
Breasts in general will be enlarged, hard, and uncomfortable because of the increased blood supply to the breasts along with the production of milk. But sometimes breast enlargement can cause pain so that the mother's milk does not come out freely. This study aims to determine the combination of papeda and katuk leaves on the smooth production of breast milk. Quasi-experimental research In the experimental and control groups (n=20) selected using the Cluster Random Sampling technique with the criteria of postpartum mothers who were treated for at least 3 days, gave breast milk with a frequency of fewer than 12 times in 1 day and did not experience psychological disorders. The instrument used is an observation sheet. the provision of warm papeda (Metroxylon sp) compresses with the addition of Sauropus Androgynus was given 2 times, in the morning and evening for 7 days. Data analysis using the Mann Whitney test. The Mann-Whitney test showed a significant difference between the treatment group and the control group, with a P-value of 0.000 which was P <0.05. The conclusion of this study is that there is a significant effect of warm papeda compresses by mixing Sauropus Androgynus on the smooth production of breast milk.